Current state and restoration of sea trout and Atlantic salmon populations in three river systems in the eastern Gulf of Finland - Peuhkuri, Nina; Saura, Ari; Koljonen, Marja-Liisa; Titov, Sergey; Gross, Riho; Kannel, Risto; Koskiniemi, Jarmo (My University, 2014)
We investigated by electrofishing the state of sea trout population and also the fish assemblage as a whole in two Finnish–Russian cross-border river systems, Mustajoki/Tchornaja/Soskuanjoki/Malinovka and Hounijoki/Buslovka/Rakkolanjoki/Seleznevka, draining into the Gulf of Finland. Based on the fish assemblage, we assessed the ecological status of the rivers. In the third of our target river systems, Gladyshevka/Rotshinka in the Karelian Isthmus, our interest was particularly focused on the Atlantic salmon population. In Mustajoki/Tchornaja/Soskuanjoki/Malinovka, trout dominated in density the upper reaches and small tributaries, their densities decreasing towards the river mouth. Restoration of rapids led to increased trout densities, but benign weather conditions may partly explain the trend. The trout population in this river system was found to be genetically unique and diverse. In Hounijoki/Buslovka/Rakkolanjoki/Seleznevka, only a few trout were found − from the Russian side. The absence of trout, especially from the upper reaches, is due to migration obstacles but also probably to poorer water quality compared to Mustajoki/Tchornaja/Soskuanjoki/Malinovka. This was also reflected in the poorer ecological status. In Gladyshevka/Rotshinka, both salmon and trout were caught from the River Gladyshevka, but neither of these from the River Rotshinka. The densities of salmon in the River Gladyshevka partly reflect the releases of hatchery fish. We established a broodstock of the Mustajoki/Tchornaja/Soskuanjoki/Malinovka trout to enhance restoration of this native sea trout population still found on both the Finnish and Russian sides of the cross-border riversdraining into the Gulf of Finland. We also transferred wild-caught trout to the River Soskuanjoki on the Finnish side and upper reaches of the River Malinovka on the Russian side to promote the existence of the population in the whole river system in the wild. Later observations of trout from the Finnish side suggested that trout accepted the area. We also analysed in which proportions trout from different native or hatchery populations around the Gulf of Finland are represented in the Finnish coastal sea trout catch. Genetic analyses indicated that at least 75% of the catch originated from Finnish hatchery releases, and at least 20% of the catch consisted of wild trout, mostly from Estonia. Trout from the cross-border rivers represented only about 1% of the total catch. Scale analysis of a sample of captured trout indicated that individuals were caught young and often undersized. The salmon releases into the River Gladyshevka started over a decade ago were continued during the project. Salmon were also released into the River Rakkolanjoki. A sample of released salmon was additionally tagged with T-bar anchor tags prior to release to gain information on their migration based on tag recoveries. Seven tags have so far been recovered.

; Selvitimme sähkökoekalastuksin meritaimenkantojen tilaa sekä kalastoa kahdessa Suomen ja Venäjän rajajokivesistössä, Mustajoki/Tchornaja/Soskuanjoki/Malinovka ja Hounijoki/Buslovka/Rakkolanjoki/Seleznevka, jotka laskevat Viipurinlahteen itäisellä Suomenlahdella. Arvioimme kalastoon perustuen jokivesistöjen ekologisen tilan. Kolmas hankkeen kohdevesistö, jossa mielenkiintomme kohteena oli erityisesti merilohi, oli Karjalan kannaksella sijaitseva Gladyshevka/Rotshinka, joka on tärkeä merilohen palauttamiskohde itäisellä Suomenlahdella Venäjän puolella. Taimenen poikastiheydet ylittivät Mustajoki/Tchornaja/Soskuanjoki/Malinovka -jokivesistössä muiden kalalajien tiheydet erityisesti latvavesissä sekä sivu-uomissa. Taimentiheydet laskivat jokisuulle mentäessä. Taimenen poikastiheydet kasvoivat tutkimuksen aikana kunnostetuilla koskilla. Osittain kasvu voi selittyä taimenen lisääntymiselle ja poikasille suotuisilla sääolosuhteilla. Mustajoki/Tchornaja/Soskuanjoki/Malinovka -jokivesistön taimenkanta osoittautui perinnöllisesti ainutlaatuiseksi ja monimuotoiseksi. Hounijoki/Buslovka/Rakkolanjoki/Seleznevka -jokivesistöstä löytyi vai jokunen taimen Venäjän puolelta. Taimenen puuttuminen erityisesti jokivesistön yläosista selittyy nousuesteillä, mutta osittain myös veden Mustajoki/Tchornaja/Soskuanjoki/Malinovka -jokivesistöä heikommalla laadulla. Tätä heijasti myös havaittu huonompi ekologinen tila. Gladyshevka/Rotshinka -jokivesistöstä saatiin sekä lohta että taimenta Gladyshevka-joesta, mutta Rotshinka-joesta ei lajeista kumpaakaan. Glahyshevka-joessa havaitut lohitiheydet selittyvät osittain jokeen tehdyillä lohi-istutuksilla. Mustajoki/Tchornaja/Soskuanjoki/Malinovka -jokivesistön taimenesta perustettiin viljelyyn emokalasto tämän ainoan Suomen ja Venäjän puolelta Viipurinlahteen laskevista rajajoista tavatun alkuperäisen meritaimenkannan säilyttämiseksi ja suojelemiseksi. Villejä taimenia siirrettiin myös Soskuanjokeen ja Malinovka-joen yläosiin taimenkannan olemassaolon turvaamiseksi koko jokivesistön alueella. Soskuanjoesta myöhemmin tehtyjen havaintojen perusteella taimenet hyväksyivät siirtoalueen. Selvitimme myös, miten luonnontaimenkannat ja laitoskannat ovat edustettuina Suomen rannikon taimensaaliissa. Geneettiset analyysit osoittivat, että vähintään 75 % saaliista on peräisin laitoskannoista. Ainakin viidennes saaliista oli peräisin luonnonkannoista, enimmäkseen Viron puolelta. Rajajokiemme taimenten todettiin muodostavan taimenen kokonaissaaliista vain n. 1 %. Suomuanalyysit osoittivat taimenten jäävän saaliiksi nuorina ja usein alamittaisina. Yli vuosikymmen sitten aloitettua istutuksin toteutettua merilohen elvytysprojektia Gladyshevka-joella jatkettiin tässä hankkeessa. Merilohta istutettiin myös Rakkolanjokeen. Istukkaita myös merkittiin t-ankkurimerkein ennen vapautusta vaellustietojen kartuttamiseksi. Palautustiedot on saatu tähän mennessä seitsemästä merkistä.
Meritaimen- ja lohikantojen tila ja elvyttäminen kolmessa itäisen Suomenlahden jokivesistössä
Sout-East Finland - Russia ENPI CBC 2007-2012 Contact person: Nina Peuhkuri
Keywords: Sea trout; Atlantic salmon; cross-border rivers; electrofishing; DNA analysis; ecological status; geneettinen analyysi; merilohi; Gulf of Finland; Suomenlahti; meritaimen; sähkökalastus; DNA; ekologinen tila